The economic costs and benefits of a participatory project to conserve maize landraces on farms in Oaxaca, Mexico - Smale, Melinda; Bellon, Mauricio R.; Aguirre Gómez, José Alfonso; Rosas, I. Manuel; Mendoza, Jaime; Solano, A. M.; Martínez, R.; Ramírez, Alejandro; Berthaud, Julien (Wiley, 2003)
Conventional methods were used to assess the benefits and costs of an unconventional project whose purpose was to test whether participatory crop improvement can encourage Mexican farmers to continue growing maize landraces by enhancing their current use value. Findings suggest that farmers as a group earned a high benefit‐cost ratio from participating, though from the perspective of the private investor the returns were low. The project also generated social benefits, but these would be difficult (and costly) to measure. There was a gender bias in both participation and benefits distributions, though there is some evidence of a welfare transfer to maize deficit households. Application of other valuation approaches will be necessary in order to assess both the private and social benefits of similar projects.